Interdisciplinary action of nurses to children with suspected sexual abuse - Lia Leão Ciuffo; Benedita Maria Rêgo Deusdará Rodrigues; Florence Romijn Tocantins (Universidad de Antioquia, 2014)
Objective. Understanding the role of nurses as members of interdisciplinary teams in the care of children with suspected sexual abuse. Methodology. This is a qualitative research based on the sociological phenomenology of Alfred Schutz. In 2008 were interviewed eleven nurses who worked in reference institutions for the care of child victims of sexual abuse in Rio de Janeiro. Results. The category called 'Interacting with other professionals in child care' emerged from the analysis of performance of professionals. The intersubjective relations between the nurses and the interdisciplinary team will enable to understand the intent of care from the perspective of social, emotional and psychological needs of children and their families. Conclusion. Interdisciplinarity favored the development of actions based on acceptance, listening and agreements on possible solutions in the care of children with suspected sexual abuse.